Developing Students' Coaching Ability Through Peer Coaching. (February 2020) - Eriksen, Matthew; Collins, Sarah; Finocchio, Bailey; Oakley, Julian
Our study adds to the existing literature by documenting an improvement in students' coaching effectiveness over the course of the semester, as well as identifying the most important factors contributing to this improvement. We identify the rationale for the development of the peer coaching process and its learning objectives, as well as describe the employment of the peer coaching process. We found that training, structured peer-feedback, supporting handouts, and consistent practice of peer coaching were the most important factors to becoming an effective peer coach. The most challenging factors to students in becoming an effective peer coach were developing their ability to effectively listen to their peers and the fear associated with asking their partner challenging or probing questions. Rather than listening, students found themselves interjecting their opinions, offering advice, talking about themselves, or relating what their partners were saying to their own lives, if only in their minds. We found the most effective aspects of students' peer coaching in supporting peers' leadership development were being nonjudgmental, listening, accountability, and asking questions. We present suggestions to prepare instructors and students to employ a peer coaching process, as well as possible adaptations.